INNOVATION IN ISLAMIC EDUCATION - Mohamed Mohamed Tolba Said; Krishnan Umachandran; Abdul Ghafar Don (Universitas Negeri Jakarta, 2018)
The approach to religious education had been shaped by historical, cultural, social, and political reasons, however, both the inherited secular education system and traditional religious education system, as standalone, can never bring development to the society. Hence, the religious education must be combined with secular education and the innovative approaches in education evolve continuously to uphold the pedagogy, learning approaches and facilities even in the current context to sustain, endure to be relevant and culturally resilient with the contemporary scientific and advanced technology. The process of education evolved in many countries, radically changed from traditional madrasah to localized vernacular schools, and then on to European education. The educational curriculum should kindle the learning process by systematic observation, quantitative reasoning and scientific expressions. The learning tools should engage students with the creation through observation, pictorial and descriptive records, exploration, articulation, and communication with fellow students. This paper analysis a combination of both structural and cultural orientations on identified needs leading to facilitations in learning environment, implementing knowledge to practice, and finally evaluated for the fulfillment or gap identification, for furthering the learning or development inputs towards constructive utilization and growth.